Neoliberal Control Mechanisms and Their Impact on Islamic Educational Governance - Findi Alexsandy; Irawan; Rohmat Mulyana Sapdi; Cep Mulyana (Journal of Educational Management Research, 2025)
Islamic education in Indonesia is increasingly confronted with neoliberal governance that emphasizes efficiency, accountability, and competitiveness, potentially marginalizing its spiritual mission. This study aims to examine how neoliberal control mechanisms and knowledge capitalism operate in madrasah governance and how Islamic educational values respond to these pressures. Employing a descriptive qualitative approach with a single case study design, the research was conducted at MTsS Al-Maziyyah Cilaku, Cianjur Regency. Data were collected through semi-structured interviews, documentation, and indirect observation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that accreditation systems, national assessments, performance reporting, and bureaucratic supervision significantly shape institutional management, reflecting neoliberal control and knowledge commodification. The madrasah demonstrates adaptive capacity by internalizing Islamic values such as amanah, ihsan, and ikhlas as ethical foundations of managerial practice. This study concludes that Islamic educational institutions are not passive recipients of neoliberal pressure but active agents capable of negotiating it through “managerial soft resistance.” The study contributes theoretically by enriching Islamic educational management discourse with an empirical model that integrates spirituality, professionalism, and critical engagement with neoliberal education policies.